Mycocoenologic study of the macrofungi on the forest of Jbel elbir (Aïn Draham, Jendouba, Tunisia) - Ben Hassine Ben Ali, Mourad; Aschi-Smiti, Samira; Ben, Mourad; Ben, Hassine (African Journal of Ecology, 2013)
Macrofungi have important functions in forest ecosystems. It is essential to have information about these species to ensure proper management of such ecosystems. Due to the importance of forestry in Tunisia and the lack of information on fungal communities, this study was conducted in North Western of Tunisia. The objective was to enumerate macrofungal diversity in relation to various environmental factors. In total, 158 fruiting bodies were collected and 60 species were identified. Among them, 39 species are mycorrhizal. A fruiting body is the first visible appearance of the spore-bearing surface until its disintegration. More fruiting bodies were found on the eastern slopes than on the western slopes. This reflects the distribution of tree species and soil type. Almost all fungal species were collected from soils of moderate acidity (pH 4–pH 5), 5 species from soils with low acidity (pH 5–pH 6.8), and only 3 species from soils with high acidity (pH < 4). The majority of fruiting bodies occurred in soils with a percentage of organic matter ranging from 1 to 5 and a phosphorus content ranging from 15.1 to 20 ppm.
Keywords: Altitude; exposure; Macrofungi; mycocoenology; organic matter; pH; Tunisia

Coenological research on macrofungi in evergreen oak woods in the hills near Siena (Italy) - Dominicis, V; Barluzzi, Carla (Plant Ecology, 1983)
For a mycocoenological study of macromycetes in Mediterranean evergreen forests in the Sienese pro- vince, five stands belonging to the Quercion ilicis have been observed during more than two years. The phytosociological analysis of these evergreen oak woods, situated at the limit of the geographical distribution of the alliance, reveals them as intermediate between the typical Mediterranean vegetation and the sub-Mediterranean deciduous broad-leaved forests. 181 fungal species were recognized and assigned to seven ecological groups on the basis of substratum, habitat, forest management and/or particular mycorrhizal relationship. Our results have been compared with those obtained in some European deciduous forests. Such a comparison shows the occurrence of 16 thermophilous fungal species in the Siena woods which are missing or very rare in the European deciduous forests. On the basis of our present knowledge, five of these species ( Boletus lepidus, Hygrophorus dichrous, Hygrocybe nigrescens, lnocybe similis, Phellinus torulosus) may be considered as strictly tied to the evergreen oak woods. Five others, which have been reported for several European phytocoenoses, seem to be 'preferential taxa' of our evergreen oak woods, namely: Cortinarius calochrous, C. sodagnitus, Hygrophorus arbustivus, H. russula, Lyophyllum immundum. On the whole the highest similarities have been found with the more xerothermophilous European forests (Querco-Lithos- permetum and Sorbo-Quercetum). The presence in the Quercus ilex woods of numerous more mesophilous fungi, some of which are widespread in beech forests, underlines the transitional nature of the phytocoenoses studied.
Keywords: fungi; macromycetes; mycocoenology; phytosociology; quercus ilex coppices; toscana